Land use planning of the Bara tract area under Sardar Sarovar Canal Command of Gujarat - Chinchmalatpure, Anil R; Nayak, A K; Rao, G Gururaja (Indian Farming, 2015)
Productivity of the salt-affected black soils of the Bara tract area is not fully utilized because of raditional cultivation. The major soils of Bara tract are deep black clayey soils with montmorrillonite as dominant clay mineral with high water holding capacity. These soils have significant concentration of soluble salts in sub-soils, although the concentration in the surface layer is low. It was found that 40% of surface soils are free from salinity (<2 dS/m), 49% soils are saline (2-4 dS/m) and only 11% soils have a salinity greater than 4.0 dS/m. On the other hand 10% of the sub-soils are having salinity less than 2 dS/m, 15% between 2-4 dS/m and 75% greater than 4 dS/m. Land evaluation study was carried out in the Bara tract under Sardar Sarovar Canal Command area. Land evaluation is a crop specific suitability system and it provides information on the opportunity and constrains for the use of land as a basis for making decision on its use and management. Such evaluation is a prerequisite for land use planning because it helps in taking decision on land utilization types which are sustainable and ecofriendly. In the present study, for soilsite suitability classification, the limitation approach is used which refers to the deviation of land characteristics from optimal condition that adversely affects the land use for specific purpose, the suitability of these soils was evaluated for the cotton and wheat crops. The information on the soil-site suitability of crops, especially on the threshold values of soil-site parameters influencing performance of a land use system can help in taking decision for planning.